2012
DOI: 10.1302/2046-3758.16.2000008
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of two different locking compression plates in the volar fixation of complex articular distal radius fractures

Abstract: ObjectivesTo investigate the differences of open reduction and internal fixation (ORIF) of complex AO Type C distal radius fractures between two different models of a single implant type.MethodsA total of 136 patients who received either a 2.4 mm (n = 61) or 3.5 mm (n = 75) distal radius locking compression plate (LCP DR) using a volar approach were followed over two years. The main outcome measurements included motion, grip strength, pain, and the scores of Gartland and Werley, the Short-Form 36 (SF-36) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
0
15
0
2
Order By: Relevance
“…Screw-plate failure, i.e. screw push-out, is a known complication following polyaxial VLPO [ 36 , 37 ]. To our best knowledge, no biomechanical study has yet analysed this failure mode.…”
Section: Discussionmentioning
confidence: 99%
“…Screw-plate failure, i.e. screw push-out, is a known complication following polyaxial VLPO [ 36 , 37 ]. To our best knowledge, no biomechanical study has yet analysed this failure mode.…”
Section: Discussionmentioning
confidence: 99%
“…Thielke et al 8 treated 49 displaced articular fractures with the overall outcome on Gartland and Werley scales being 85% excellent to good scores. Similarly, Recum et al 9 showed 96% and 86% excellent to good in 2.4 mm and 3.5 mm LCP respectively. We had comparable results of 85% in excellent to good category [ Table 5 ].…”
Section: Discussionmentioning
confidence: 77%
“…According to Knirk and Jupiter, 3 these fractures must always be separated from extra-articular fractures as their response to treatment and the functional outcomes are always quite distinct. Thielke et al 8 used fixed angle plates and von Recum et al 9 used 2.4 and 3.5 mm LCP for fixation of these fractures. Extra-articular comminuted fractures (type A2 and A3) are inherently prone to re-displacement after closed reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The range of motion (ROM) and grip strength were used to evaluate the wrist's function. The physician-based Gartland-Werley score [8] and the patient-reported DASH (disabilities of the arm, shoulder, and hand) score system [9]were used to indicate the overall functional outcome. Before the culture results, chemotherapy was administered for 2 weeks with four oral anti-tuberculous agents: isoniazid 5 mg/kg, rifampicin 10 mg/kg, pyrazinamide 20 mg/kg, and ethambutol 15 mg/kg per day.…”
Section: Patients' Datamentioning
confidence: 99%